The Application of Al-Ghazâli’s Tasawuf Ethic to Actualize Good Governance in Indonesia - Agus Iswanto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
This article tries to explore the possibilities of tasawuf ethic application to actualize Good Governance in Indonesia. The study focuses on some arguments why tasawuf and al-Ghazali are selected as the main discussion. The arguments are that Tasawuf is an Islamic tradition and al-Ghazali has capability for it in terms of his social lives. He proposed three concepts of thought concerning tasawuf ethics, that is, zuhd, teleological ethics, and ummahat al-fadhail. These concepts can be implemented in reforming good Indonesian government.Keyword: Tasawuf, social sensitivity, Ilâhiyah consciousness, tasawuf tradition